Developmental Outcome of Children with Cerebral Palsy after Feeding and Seating Intervention - Bashar, Md Khairul; Iqbal, Shahed; Chowdhury, Mahmood Ahmed; Das, Dhananjoy; Iqbal, Md (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Cerebral Palsy (CP) is a diagnostic term used to describe a group of permanent disorders of movement & posture causing activity limitation that are attributed to non progressive disturbances in the developing fetal or infant brain. The motor disorders are often accompanied by disturbances of sensation, perception, cognition, communication and behavior as well as by epilepsy, secondary musculoskeletal problem and feeding difficulties. Aims: To see the development of a child with cerebral palsy after comprehensive feeding & seating intervention. To recommend measure for reducing neurodevelopmental problems. To improve mother- child interaction. Methods: This hospital based prospective cross sectional observational study was done in Child Development Center (CDC) of the Department of Pediatrics, Chattagram Maa Shishu-O-Genaeral Hospital (CMSOGH), Chittagong from July 2013 to December 2013. Children with Cerebral palsy aged 1-15 years included in this study. Results: Most of the patients (60%) before intervention were having only liquid food. After intervention most of the patients were having either a combination of semi-solid and solid food (48%) or only semi-solid food (42%). After intervention 80% of patients were sitting during feeds which was only 12% before intervention. After intervention feeding time is reduced to 15 to 30 minutes which was 30 min to one hour. Most of the patients (90%) never ate by themselves before intervention, only 4% were selffed. After intervention 56% were self feeding for some part of the meal & 24% were self feeding at every meal. Conclusion: Feeding problems in children with cerebral palsy are common. Simple home based measure, like feeding and seating intervention, should be carried out under the guidance of Child Development Center run by developmental therapist with assistance from pediatricians & child psychologists in order to improve the development of the child with cerebral palsy as well as the quality of life. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22872 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 11-14